Electronic structure of 2H-SnSe₂: ab initio modeling and comparison with experiment - Bletskan, D.I.; Glukhov, K.E.; Frolova, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Energy band structure, total and local partial densities of states, spatial distribution of electronic density of 2H-SnSe₂ have been calculated using the densitym functional theory method in LDA and LDA+U approximations both with and without consideration of spin-orbit interaction. From the band structure calculation results, it follows that 2H-SnSe₂ is an indirect-gap semiconductor. The calculated band structure is compared with the dispersion curves E(k) plotted using the known measurement results of angular dependent photoemission spectra. It has been observed the good agreement between theoretical and experimental dispersion curves. The calculated total and local partial densities of states have been compared with the known experimental data obtained using XPS, UPS, ARXPS, BIS methods.